MedThaiVis: An approach for Thai biomedical data visualization - Jarernsri Mitrpanont (2018)
© 2017 IEEE. Biomedical information is highly complex, scattered in all areas, and difficult to present therefore the medical and public health practitioners or professionals who are working with these data are required to interpret numerous biomedical data sets. Moreover, these data are vital, abundant and change at any time. With the proper tools and guidelines to visual this information, the knowledge sharing and disseminating are increased among the health practitioners, experts and decision makers. It also helps to release some load of works from the experts who are required to interpret each data set which not only very time-consuming but may also miss critical findings from these complex information. This paper proposes an effective approach of data visualization to manage and visualize biomedical information of the R2R Thailand project. The proposed techniques support various type of visualization techniques namely 1) Dashboard 2) Medical and Healthcare Map 3) Multi-relationship Network and 4) Statistic Graph. The result of the proposed approach yields 87.33% for the average correctness of the meaning interpretation and understanding which is satisfactory and effective for biomedical information knowledge sharing.